Karakteristik Habitat Perkembangbiakan Vektor Filariasis di Kecamatan Kodi Balaghar Kabupaten Sumba Barat Daya - Mefi Mariana Tallan; Fridolina Mau (Loka Litbang Kesehatan Pangandaran, 2016)
Subdistrict scores balaghar is on filariasis endemic areas in the shouthwest district Sumba. Filariasis (elephantiasis) is a chronic infectious disease caused by the filarial worm that attacks the lymph channels and lymph (lymphatic system) that can cause acuteor chronic clinical symptoms and is transmitted by mosquitoes Mansonia, Anopheles, Culex, Amigeres. The purpose researchis to describe the characteristics of the environment and behavior to the incidence on filariasis in District Kodi Balaghar South western Sumba. This research is descriptive study with cross sectional approach that describes the spread of filariasis. Kodi was conducted in Southwest Sumba Regency Balaghar for eight months from April to November 2014. Foundas apotential habitat forlas mosquito breeding habitats where dominant is a puddle of water, springs, drains and small stream swith temperatures ranging from21-350C, from 0,22 to 795 luxillumination, range pH between7,2 to 7,7, 0-0.1‰ salinity with elevation ranging from 25-117m/asl. Where is thespecies found in the breeding habitat on is An.vagus, An.barbirostris, An.annularis, Cx.vishnui, Cx.bitaeniorhynchus, Cx.quinquefasciatus, Ar. Kuchingensis.